1999
DOI: 10.1002/(sici)1098-1128(199907)19:4<295::aid-med3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of phospho-tyrosine signaling complexes

Abstract: A structural basis for activation and substrate specificity of src tyrosine kinases, and regulation of protein–protein association by tyrosine phosphorylation is described. Lyn, a src‐family tyrosine kinase, recognizes and phosphorylates the immunoreceptor tyrosine‐based activation motif, ITAM, a critical component in transmembrane signal transduction in hemopoietic cells. The structure of an ITAM peptide substrate bound to an active form of Lyn tyrosine kinase was determined by high‐resolution NMR, and a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This low‐affinity interaction occurs through the amino‐terminal region of Src kinases independently of ITAM phosphorylation and is distinct from SH2‐mediated binding of Src kinases to phosphorylated ITAMs (6–8). As initial ITAM phosphorylation is thought to occur at the amino‐terminal tyrosine (9), support also comes from structural studies that indicate that side chains of the hydrophilic residue upstream of the amino‐terminal tyrosine of the immunoglobulin α (Igα) ITAM make several hydrogen bonds with the Src family kinase member Lyn (10). The importance of this interaction was demonstrated upon mutation of this hydrophilic residue, which abolished Lyn binding in an enzyme assay (11).…”
Section: What Defines An Immunoreceptor Tyrosine‐based Activation Motif?mentioning
confidence: 99%
See 1 more Smart Citation
“…This low‐affinity interaction occurs through the amino‐terminal region of Src kinases independently of ITAM phosphorylation and is distinct from SH2‐mediated binding of Src kinases to phosphorylated ITAMs (6–8). As initial ITAM phosphorylation is thought to occur at the amino‐terminal tyrosine (9), support also comes from structural studies that indicate that side chains of the hydrophilic residue upstream of the amino‐terminal tyrosine of the immunoglobulin α (Igα) ITAM make several hydrogen bonds with the Src family kinase member Lyn (10). The importance of this interaction was demonstrated upon mutation of this hydrophilic residue, which abolished Lyn binding in an enzyme assay (11).…”
Section: What Defines An Immunoreceptor Tyrosine‐based Activation Motif?mentioning
confidence: 99%
“…Additionally, phage display libraries have demonstrated that Src family kinase members have different preferred substrates (26). While Lyn was shown to require the upstream D/E of Igα(10), other members of the Src kinase family may have different or less stringent requirements for this upstream residue, a possibility that remains to be formally tested.…”
Section: What Defines An Immunoreceptor Tyrosine‐based Activation Motif?mentioning
confidence: 99%
“…As mentioned above, there are no crystal structures of Src or Src family kinases with peptide substrate bound to the active site. However, Post et al52 have determined the substrate conformation of the ITAM peptide (DENLYEGLNLDD) bound to the Src family PTK, Lyn, using transferred nuclear Overhauser effect (NOE). In this structure, tyrosine is positioned next to Asp 181 (c‐src numbering).…”
Section: Discussionmentioning
confidence: 99%